A multi-smart agent-based training environment for enhancing 3D graphics production and design thinking skills among elementary computer teachers - Sorour, Shaymaa E.; Ahmed, Rahma J. M.; Abd El Aziz, Mahmoud I. (Frontiers in Education, 2024)
This study introduces a multi-smart agent-based training environment aimed at enhancing the production of 3D graphics and fostering design-thinking skills among primary-stage computer teachers. This environment offers a collaborative and interactive learning experience using intelligent agents represented as animated characters. The research evaluates the effectiveness of this innovative training approach through experimental groups, demonstrating significant improvements in the cognitive and psychomotor domains of 3D graphics production skills and in developing design thinking. The results underscore the potential of smart agent technology in educational settings, offering a dynamic platform for teacher professional development by integrating modern technological tools and creative problem-solving methodologies. This study pioneers using multi-smart agent environments in primary education, providing a novel framework that significantly enhances educators' skills and prepares them for future technological advancements in teaching.